دراسة بعض خواص الترب المتشكلة على صخور كلسية في منطقة بانياس وتصنيفها (Latakia University Journal -Biological Sciences Series, 2013)
تناول هذا البحث دراسة بعض خصائص الأتربة المتشكلة على صخور كلسية تحت غطاء نباتي طبيعي من عريضات الأوراق (بشكل رئيسي: السنديان العادي Quercus calliprinos والسنديان البلوطي Quercus infectoria) في منطقة بانياس على ارتفاع بين 234-63 م عن سطح البحر. نفذت ثلاث مقاطع ترابية في المنطقة المدروسة، ووصفت مورفولوجيا وحدد نوع الغطاء النباتي وبيانات تحديد الموقع GPS لكل مقطع. أخذت العينات من آفاق كل مقطع، وأجري عليها بعض التحاليل الفيزيائية والكيميائية (القوام، الكثافة الظاهرية والحقيقية، كربونات الكالسيوم الكلية، محتوى المادة العضوية، السعة التبادلية الكاتيونية، الكالسيوم والمغنيزيوم المتبادلين، ودرجة الحموضة pH). تبين من خلال الدراسة أن عمق التربة يتراوح بين المنخفض والمتوسط (60 – 137) سم، أما درجة الـ pH فقد تراوحت بين المتعادل والقلوي (7.1 – 8.2)، في حين كان محتوى كربونات الكالسيوم مرتفعا في كامل المقطع (17 – 88)%، وكذلك محتوى المادة العضوية في الآفاق السطحية (8 – 12)%، بينما كانت السعة التبادلية الكاتيونية مرتفعة (21 – 92 م.م/100غ ) نتيجة ارتفاع المحتوى من المادة العضوية والطين (18 – 74%)، ولوحظ سيادة الكالسيوم على سطح معقد الادمصاص (17 – 74 م.م/100غ) ثم تلاه المغنيزيوم (0.2 – 6م.م/100غ). تتبع الترب المدروسة من الناحية التصنيفية للرتب : Entisols , Mollisols , Inceptisols. وقطاعاتها من النوع:  A – (B) – C ، A – AR – R ، A – AC – C. تفاوت عمق التربة ومحتواها من القطع الصخرية كثيرا وذلك بحسب درجة الانحدار وكثافة الغطاء النباتي وصلابة الصخور الأم. كما بينت النتائج أن معظم خواص التربة موروثة من مادة الأصل، والترب ضعيفة التطور وحديثة التكوين. This research studies some soil properties formed on calcareous rocks under a natural  plant  cover  of  wide  leaves  (mainly:  Quercus  calliprinos and  Quercus   infectoria) in Banias region (63 – 234) meters height above sea level. Firstly, 3 soil profiles in the studied area were done, then morphological characteristic, type of plant cover and Geographic Position System (GPS) were accomplished. Samples were taken from profile horizons, then, physical and chemical properties were determined (structure, bulk and real densities, total calcium   carbonate   percent,   organic  matter  content,  action  exchange  capacity,  exchangeable calcium and magnesium, and pH). The profile depth ranged between low and medium (60 – 137) cm, the pH ranged between neutral and alkaline (7.1- 8.2), there was an increase in calcium carbonate content in the whole profile (17- 88%), and also increase of organic matter contents in the horizon (8- 12%). Due to high clay (18-74) % and organic matter content (8-12) %, the soils showed high cation exchange capacity (CEC) (21- 92 meq/100g). Exchangeable calcium was dominant on the surface of adsorption complex (17- 74 meq/100g), then magnesium in second stage (0.2- 6 meq/100g). From a classification point, the soils were classified under the following orders: Entisols, Mollisols, Inceptisols, which have profile types: A – AC – C, A – AR – R, and A – (B) – C. Soil depth and its content of rocky pieces were varied according to relief degree, plant cover intensity, and parent rocks hardness. Most of soil properties are a parent material descendible, and the soils were slightly developed and recently formed.